KONSEP PENDIDIKAN JIWA DALAM PERSPEKTIF AL-QUSYAIRI - Satibi, Satibi (Tawazun: Jurnal Pendidikan Islam, 2018)
Current globalization era conveys a big wave of materialistic and anti spiritual and to evict even to replace spiritual values. The appear of spiritual problem that afflicts modern human starting from disappearence divine vision. In writing this thesis, the writers conduct library research with qualitative approach. And discusses the concept of soul education (Tarbiyah al-Nafs) of ‘Abd al-Karim Al-Qusyairi. He was a great moslem priest, expert in jurisprudence, science of kalam, science of ushul, nahwu, mufassir and a great writer.